Elgar encyclopedia on the economics of knowledge and innovation - Antonelli, Cristiano (Elgar encyclopedias in economics and finance series, 2022)
"A landmark reference work in the field, this Elgar Encyclopedia presents over 60 entries from scholars that have shaped the economics of innovation as a distinct and specialised field of investigation. Comprehensive and accessible, it further elaborates the relationship between the economics of knowledge and the economics of innovation. The Encyclopedia offers an overview of the classical origins of the early economics of technical change, and the role of Schumpterian legacies and the Arrovian economics of knowledge as indispensable ingredients to understanding innovation. The entries highlight how the analysis of the full array of feedbacks, interactions and transactions that take place within economic systems show how and why out-of-equilibrium conditions in both factor and product markets are the cause and consequence of the introduction and diffusion of innovations. This will be a critical read for economics scholars, particularly those focusing on knowledge and innovation as it offers an understanding of the definitions of key terms in the field, the founding tenets of the topic, and the economics of knowledge and innovation in more specific contexts. It will also be a useful reference tool for business school students. Key Features: - Contributions from 66 scholars in the field of the economics of knowledge and innovation - Informative table offering thematic groupings of the entries in a thorough introduction - Provides readers with the framework to elaborate innovation policies and firms strategies"--